Perioperative care in an animal model for training in abdominal surgery: is it necessary a preoperative fasting? - Alves,José Roberto (2011)
PURPOSE: Demonstrate that the rabbit may be used in the training of surgery, in addition to present its perioperative care. METHODS: Thirty two animals, with age and weight, respectively, from 3 to 5.5 months old and 3000 to 4200 grams, were undergone different periods of pre-operative fasting, exclusive intramuscular anesthesia (ketamine+xylazine), laparotomy with total gastrectomy and total splenectomy. It was dosed the pre-operative (initial) and post-surgical (end) serum blood glucose, in addition to quantify the gastric content after the resection of the part. RESULTS: The anesthetical-surgical procedure presented a mortality rate of 3.125% (1:32) and a morbidity rate of 6.25% (2:32). It was evidenced an initial mean blood glucose = 199.4 mg/dl and the end = 326.1 mg/dl. In spite of extended fasting (minimum of 2 hours for the absolute fasting and maximum of 8.5 hours for liquids, and 20.5 hours for solids) all animals presented at the end of the surgical procedure any gastric content and a blood glucose increase. Those with fasting for liquids and solids when compared to the quantity of solid gastric content, presented a moderate negative degree of correlation. CONCLUSION: The rabbit is a good model to be used in training of surgery, with a low morbi-mortality, able to be anesthetized intramuscularly, with no need of pre-operative fasting and does not present hypoglycemia even with the extended fasting period.